2010
DOI: 10.1007/s11515-010-0056-z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetics of Brugada syndrome

Abstract: Brugada syndrome (BrS) is a life-threatening cardiac rhythm disorder characterized by persistent STsegment elevation in leads V1-V3 and right bundle branch block on electrocardiograms (ECG), and by syncope and sudden death from ventricular tachycardia (VT) and ventricular fibrillation (VF). BrS is responsible for nearly 4% of sudden cardiac deaths and considered to be the most common cause of natural death in males younger than 50 years in some Asian countries. Since the first diseasecausing gene for BrS (the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…While GPD1L has been anecdotally showed to account for 11%-12% of Brugada syndrome, other studies showed no pathogenic GPD1L mutation, suggesting that GPD1L may not be a major cause of Brugada syndrome. 16,17 On the DECIPHER database (https://decipher.sanger.ac.uk/ search?q=GPD1L#consented-patients/ results), 8 other patients had deletions involving GPD1L. These were much larger deletions than in our cases.…”
Section: Gpd1l and Brugada Syndromementioning
confidence: 52%
“…While GPD1L has been anecdotally showed to account for 11%-12% of Brugada syndrome, other studies showed no pathogenic GPD1L mutation, suggesting that GPD1L may not be a major cause of Brugada syndrome. 16,17 On the DECIPHER database (https://decipher.sanger.ac.uk/ search?q=GPD1L#consented-patients/ results), 8 other patients had deletions involving GPD1L. These were much larger deletions than in our cases.…”
Section: Gpd1l and Brugada Syndromementioning
confidence: 52%
“…Whereas the prevalence of GPD1L mutations is estimated to be 11% to 12%, SCN5A mutations are found in 18% to 30% of BrS patients, and these variations currently represent the most common BrS genotype [3]. To date, approximately 300 mutations in the SCN5A gene have been described in association with BrS.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to SCN5A alterations, mutations in the glycerol-3-phosphate dehydrogenase 1-like ( GPD1L ) gene cause abnormal trafficking of the cardiac sodium channel to the cell surface and a reduction of approximately 50% of the inward sodium current. To date, mutations in the SCN5A and GPD1L genes are estimated to account for approximately 18% to 30% and 11% to 12% of BrS probands, respectively; the prevalence of variants in other disease-related genes (such as CACNA1C , CACNB2 , SCN1B , KCNE3 , SCN3B , and HCN4 ) is yet unknown [3]. …”
Section: Introductionmentioning
confidence: 99%
“…Another study [ 36 ] showed that the GPD1-L mutation itself causes a loss function of enzymatic activity, and decreased GPD1-L activity would have then increased the substrate G3P, and fed the PKC-mediated phosphorylation of SCN5A at S1503 where such phosphorylation was known to decrease I Na . A study showed that GPD1-L gene accounted for 11%–12% BrS probands [ 37 ], but other studies showed no identification on any missense GPD1-L gene mutation, suggesting that GPD1-L may not be a major cause of BrS [ 38 , 39 ]. Further studies are needed to obtain the accurate prevalence of GPD1-L variants in BrS.…”
Section: Genetic Factors Of Brsmentioning
confidence: 99%